Water is life: politics, memory and experience in mining conflicts in Cajamarca, Peru - Penãfiel, Adriana Paola Paredes; Radomsky, Guilherme Francisco Waterloo (Revista de Antropologia, 2021)
In this article we analyze the defense of life and water in social and environmental conflicts in the region of Cajamarca, northern Peru. In recent years the contention over water has become a central issue in people's lives in a region whose main focus is mining exploration and for which discourses and appeals are used to evoke the benefits of development that it can bring about. Through ethnographic research, we witnessed the efforts of people and collectives to defend the waters of rivers, lagoons and irrigation channels in the Andes in parallel to the way they defend life. In doing so, they articulate memories, local knowledge and collective experiences to disrupt the roles that the conventional political order has assigned to them. They creatively enact their own ways of thinking and articulate life projects, resisting to the opulence of mining companies or state authorities.